Synthesis of Atropisomeric Two‐Axis Systems by the Catalyst‐Controlled syn‐ and anti‐Selective Arene‐Forming Aldol Condensation. Issue 24 (11th April 2022) - Moser, Daniel; Sparr, Christof
Abstract: Simultaneous control over the configuration of multiple stereocenters is accomplished by numerous catalytic methods, providing a reliable basis for the synthesis of stereochemically complex targets in isomerically defined form. In contrast, addressing the configurations of multiple stereogenic axes with diastereodivergent catalyst control is thus far only possible by stepwise approaches. Herein we now describe that all four stereoisomers of atropisomeric two‐axis systems are directly tractable by assembling a central aromatic unit of teraryls through an arene‐forming aldol condensation. By using cinchona alkaloid‐based ion‐pairing catalysts, the four feasible reaction pathways are differentiated from identical substrates under defined basic conditions without preactivation, thus enabling complete stereodivergence with enantioselectivities of up to 99 : 1 e.r. Abstract : The complete stereochemical addressability for all atropisomeric enantio‐ and diastereomers is viable by converting diketo substrates with simultaneous control over two configurationally stable stereogenic axes. The atropisomeric two‐axis systems were prepared by the direct catalyst‐controlled arene‐forming aldol condensation using cinchona alkaloid‐based ion‐pairing catalyst with up to 99 : 1 e.r.